Association between familial risk and caries risk in 5 year old scholars - Carlos da Rocha SANTOS; Flávia Martão FLÓRIO; Luciane ZANIN (Faculdade São Leopoldo Mandic, 2018)
Objective: This study aimed to evaluate the association of familial social risk and caries risk in 5-year-old school students from the municipality of Coari. Methods: The sample consisted of 361 students from 3 schools in the city. Data were collected from file A of the Basic Attention Information System and from records of families enrolled in Family Health Units for the classification of families according to Family Social risk and caries risk was classified according to the Secretary of Health of São Paulo. A descriptive data analysis and a multiple logistic regression were performed to verify the possible association of family social risk with family social risk and demographic variables. Results: The results showed that 51% of the sample were female, the prevalence of caries was 67.6%; and dmf-t 3.16. There was an association of high social risk with prevalence, and high risk of caries. Conclusion: Therefore, children at high risk of caries were more likely to belong to families with higher social risk. Thus, this research indicates that the present tool for assessing family social risk can be used in other studies related to planning, organization and access to oral health services.